2019
DOI: 10.3892/ol.2019.9970
|View full text |Cite
|
Sign up to set email alerts
|

circLPAR1 is a novel biomarker of prognosis for muscle‑invasive bladder cancer with invasion and metastasis by miR‑762

Abstract: Circular RNAs (circRNAs) are a specific form of non-coding RNAs, that serve a pivotal role in the development of human diseases, including Alzheimer's disease and cancer; however, only a few are known with respect to cancer. The present study identified a novel circRNA, circ lysophosphatidic acid receptor 1 (LPAR1) (hsa_circ_0087960), derived from two exons 226 base pairs in length, in muscle-invasive bladder cancer (MIBC) tissues. circLPAR1 was identified to be lowly expressed in MIBC tissues in a cohort of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 33 publications
(46 reference statements)
3
32
1
Order By: Relevance
“…In addition, it was suggested that circ_0067934 may be a therapeutic target and prognostic marker for bladder cancer, as the silencing of circ_0067934 inhibited the proliferative, migratory and invasive ability of bladder cancer cells. Notably, several other circRNAs have been reported to regulate bladder cancer, such as hsa_circ_0068871 and circRNA lysophosphatidic acid receptor 1 (20,21). Whether circ_0067934 expression is correlated with the expression of these reported circRNAs requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was suggested that circ_0067934 may be a therapeutic target and prognostic marker for bladder cancer, as the silencing of circ_0067934 inhibited the proliferative, migratory and invasive ability of bladder cancer cells. Notably, several other circRNAs have been reported to regulate bladder cancer, such as hsa_circ_0068871 and circRNA lysophosphatidic acid receptor 1 (20,21). Whether circ_0067934 expression is correlated with the expression of these reported circRNAs requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo experiments further found that Cdr1as inhibits proliferation, invasion, and migration of BCa by binding to miR‐135a . In another study, circLPAR1 was found to be downregulated in MIBC tissues . Patients with low expression levels of circLPAR1 had shorter disease‐specific survival than patients with high expression levels .…”
Section: Tumor‐suppressive Circrnas and Cancersmentioning
confidence: 90%
“…Patients with low expression levels of circLPAR1 had shorter disease‐specific survival than patients with high expression levels . At the same time, it was found that circLPAR1 affected MIBC invasion and metastasis by sponging miR‐762 …”
Section: Tumor‐suppressive Circrnas and Cancersmentioning
confidence: 99%
“…152 Moreover, circLPAR1 inhibited the activity of miR-762 by directly binding to miR-762 thereby regulating invasion and metastasis of muscle-invasive bladder cancer cells. 153 circRNA-cTFRC regulated cell invasion and proliferation through acting as a ceRNA for miR-107 to affect the expression of TFRC expression in bladder cancer cells. 154 CircUBXN7 showed to inhibit the proliferation and invasion of bladder cancer cells through binding to miR-1247-3p to elevate the expression of β-1, 4-Galactosyltransferase III (B4GALT3), which is the direct target gene of miR-1247-3p.…”
Section: Bladder Cancermentioning
confidence: 99%